Structural inequality The case of Sweden - Robling, Olof (OECD Publishing, 2017)
Structural trends not directly related to labour market functioning and redistribution have made a sizeable contribution to inequality and poverty in Sweden, but occupy only limited space in the income inequality debate. To fill this gap, we put a quarter of a century of rising inequality in Sweden in a new perspective by quantifying the effect of changing household composition, age structure, industry structure, educational attainment and immigration on inequality. The influence of structural changes on inequality is derived from micro-data from Statistics Sweden. We re-weigh subgroups of the population with certain characteristics by their population shares in 1987 to construct counterfactual income distributions for 2013 and derive inequality measures that we compare to their actual 2013 values. We find that almost half of the inequality increase between 1987 and 2013 can be mechanically ascribed to these factors
Keywords: Economics; Sweden